Teacher and Student Attendance System at Noor Faqih Usman Foundation Based on RFID Integrated with Raspberry Pi - Dhimaz Purnama Adjhi; Mohamad Rizal Hanafi; Rastra Wardana Nanditama; Rifqi Alamsya; Hafidz Rizki Fahriza; Anugrah Adiwilaga (Journal of Computer Engineering, Electronics and Information Technology, 2023)
In educational institutions, tracking attendance is crucial for ensuring effective administration and student engagement. This abstract presents the development of a Teacher and Student Attendance System at the Noor Faqih Usman Foundation, leveraging Radio Frequency Identification (RFID) technology integrated with Raspberry Pi. The proposed system aims to automate the attendance recording process, streamline administrative tasks, and enhance the overall efficiency of attendance management. This can create gaps in the development of data manipulation, data frameworks, and rigid systems. The purpose of this study was to create an RFID-Based Teacher and Student Attendance System integrated with Raspberry Pi. This study was conducted using a quantitative method of study and development study. This RFID-based attendance technology will later replace the role of paper to record the attendance of teachers and students using cards/keychains to make it easier to report attendance; data can be stored in digital form such as Excel, can be accessed via wireless smartphones, interested parties can monitor through the website, and the educational institution will be touched by at least technology. The results showed that the system was able to control the attendance process and succeeded well.